Registered Organic Farmers in Conversion to Livestock Farming inUttrakhand: Profile of Farms and Farmers - Subrahmanyeswari, B.; Chander, Mahesh (Indian Journal of Extension Education, 2010)
Organic farming as an innovation is being diffused systematically in Uttarakhand state by Uttarakhand Organic Commodity Board (UOCB), enabling farmers to market including export organic crop produce at premium prices. The livestock maintained by these organic farmers were also meeting the certain criteria of recommended organic animal husbandry standards. Therefore, in view of increasing demand for organic livestock products, the characteristics of farm and organic farmer were studied for a better comprehensive idea towards promoting organic livestock farming alongside organic crop products. A total of 180 registered organic farmers were selected through multistage sampling technique and interviewed. Most of the farmers were middle aged, with primary level of education and belongd to higher castes. Organic farming being an innovation, farmers were converting their farms on a small scale and an average farmers had 3.8 years experience in organic farming. The farmers were maintaining mostly desi breeds along with bio-diversity at genetic and species level, wherein, crop-livestock were well integrated, which is one of the objectives of organic farming. Being registered with UOCB as organic farmers, farmers were getting information on organic farming in general and package of practices on crops but to promote organic livestock farming, farmers were in need of information about organic animal husbandry standards, species-specific package of practices, timely information on export potential and processing and packing of organic livestock products for effictive marketing.